2017
DOI: 10.1051/0004-6361/201628716
|View full text |Cite
|
Sign up to set email alerts
|

Spectral disentangling with Spectangular

Abstract: The paper introduces the software Spectangular for spectral disentangling via singular value decomposition with global optimisation of the orbital parameters of the stellar system or radial velocities of the individual observations. We will describe the procedure and the different options implemented in our program. Furthermore, we will demonstrate the performance and the applicability using tests on artificial data. Additionally, we use high-resolution spectra of Capella to demonstrate the performance of our … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
(17 reference statements)
0
11
0
1
Order By: Relevance
“…Since the RVs of BAT99 32 and 77 could not be derived, we attempted their disentanglement using the code Spectangular, which is based on singular value decomposition in the wavelength domain (Sablowski & Weber 2017), first applied to WR stars in Shenar et al (2017). This procedure needs spectra spread over the orbital period and optimizes the orbital parameters or the RVs to minimize the residuals between the disentangled spectra and the observations.…”
Section: Spectral Disentanglementmentioning
confidence: 99%
“…Since the RVs of BAT99 32 and 77 could not be derived, we attempted their disentanglement using the code Spectangular, which is based on singular value decomposition in the wavelength domain (Sablowski & Weber 2017), first applied to WR stars in Shenar et al (2017). This procedure needs spectra spread over the orbital period and optimizes the orbital parameters or the RVs to minimize the residuals between the disentangled spectra and the observations.…”
Section: Spectral Disentanglementmentioning
confidence: 99%
“…The results for the spectra of the primary and secondary star showed that our method can be considered as a valid, and somewhat easier, alternative to well established codes for analysing binary stars like e.g. KOREL, FDbinary (Ilijic et al 2004) or Spectangular (Sablowski & Weber 2017).…”
Section: Discussionmentioning
confidence: 79%
“…First, three spectra that show the smallest signal from tellurics were selected from the 12 spectra listed in Tabel 1. As pointed out by Sablowski & Weber (2017), at least 3 spectra are required because SVD has to be performed on an overdetermined system of equations, that is, for two components present in the spectra, at least three observations are required. Furthermore, these spectra should correspond to distinctive orbital phases.…”
Section: Appendix B: Spectrum Of the Secondarymentioning
confidence: 99%
“…Because the correction of the telluric lines in the wavelength range under consideration is crucial for the analysis, some details of this procedure are described here. A forthcoming paper by Sablowski et al (2019) will discuss these disentangling problems in more detail.…”
Section: Appendix A: Correction Of Tellurics and Flux Ratiomentioning
confidence: 99%